Synthesis, antimicrobial, and antitubercular evaluation of new Schiff bases with in silico ADMET and molecular docking studies - Prasad, Sakshith Raghavendra; Satyanarayan, Nayak Devappa; Shetty, Avarse Satish Kumar; Thippeswamy, Basaiah (European Journal of Chemistry, 2022)
Schiff bases are a proven moiety in antitubercular drug discovery and the antitubercular drug development. Drug discovery is a never-ending process due to evolving drug resistance by the bacteria, as a result, there is a need of developing new antitubercular drugs. In this continuous process of antitubercular drug discovery, new series of Schiff bases are synthesized using quinoline carbohydrazide upon coupling with different aldehydes in ethanolic media through multistep synthesis. These synthesized compounds were purified and characterized by different spectroscopic techniques. The molecules were in vitro screened for antifungal and antibacterial potential by Agar well diffusion assay, antitubercular activity by using microplate Alamar blue assay, and an attempt has been made to study the in-silico relationship between new Schiff base derivatives 4a-f and the crystal structure of M. tuberculosis (5V3Y) protein by molecular docking studies. Synthesized compounds 4a-f show good interaction with the crystal structure of M. tuberculosis protein (5V3Y) and fulfill ADMET characteristics in silico experiments. Among the compounds tested, compound 4d was found to be active against bacteria and fungi. Compound 4b was found to be sensitive against M. tuberculosis at 50 µg/mL concentration.